Melt‐Induced Fractionation of Major Ions and Trace Elements in an Alpine Snowpack. Issue 7 (1st July 2019) - Avak, Sven E.; Trachsel, Jürg C.; Edebeli, Jacinta; Brütsch, Sabina; Bartels‐Rausch, Thorsten; Schneebeli, Martin; Schwikowski, Margit; Eichler, Anja
Abstract: Understanding the impact of melting on the preservation of atmospheric compounds in high‐Alpine snow and glacier ice is crucial for future reconstruction of past atmospheric conditions. However, detailed studies investigating melt‐related changes of such proxy information are rare. Here we present a series of five snow pit profiles of 6 major ions and 34 trace elements at Weissfluhjoch, Switzerland, collected between January and June 2017. Atmospheric composition was preserved during the cold season, while melting toward the summer resulted in preferential loss of certain species from the snowpack or enrichment at the base of the snowpack. Increasing mobilization of major ions with meltwater (NH4 + < Cl − Na + < NO3 − Ca 2+ SO4 2− ) can be related to their stronger enrichment at ice crystal surfaces during snow metamorphism. Results for trace elements show that less abundant elements such as Ce, Eu, La, Mo, Nd, Pb, Pr, Sb, Sc, Sm, U, and W were best preserved and may still serve as tracers to reconstruct past natural and anthropogenic atmospheric emissions from melt‐affected snow pit and ice core records. The obtained elution behavior matches the findings from another high‐Alpine site (upper Grenzgletscher) for major ions and the large majority of investigated trace elements. Both studies indicate that water solubility and location at the microscopic scale are likely to determine the relocation behavior with meltwater and also suggest that the observed species‐dependent preservation from melting snow and ice is representative for the Alpine region, reflecting Central European atmospheric aerosol composition. Key Points: Impurity profiles in the seasonal snowpack at Weissfluhjoch, Swiss Alps, suggest a well‐preserved atmospheric composition in winter Melting during warm periods causes preferential elution of selected major ions and trace elements from the snowpack Ammonium, the rare‐earth elements, and low concentrated trace elements tend to be most resistant to meltwater‐induced relocation